2022
DOI: 10.1111/jocn.16385
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting how parents cope with their preterm infant's pain: A cross‐sectional study

Abstract: Aims and objectives This study examined the relationships between parents' catastrophising about their infants' pain, parental self‐efficacy in the management of their infants' pain, perceived social support and the parental coping strategies for their infants’ pain‐related stress. Background Preterm infants hospitalised in the neonatal intensive care unit experience painful procedures causing stress to their parents. Coping with stress may be emotion‐ or problem‐focused. Adults' coping with their own pain has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…10 Higher self-efficacy in managing pain was associated with more effective, problemfocused coping strategies, suggesting that nurses with higher self-efficacy could better support in managing pain. [52][53][54][55] A previous study also has shown that nurse with higher self-efficacy in managing chronic pain exhibited greater confidence in performing specific pain management tasks, enhancing their overall pain management practices 53 and better adjustment and coping strategies. 54 However, the modest mediating effect of self-efficacy between knowledge, attitudes, and pain management practices suggests the presence of other influential factors not explored in the study such as patientrelated barriers, 29…”
Section: Relationship Between Knowledge Attitude and Pain Management ...mentioning
confidence: 99%
“…10 Higher self-efficacy in managing pain was associated with more effective, problemfocused coping strategies, suggesting that nurses with higher self-efficacy could better support in managing pain. [52][53][54][55] A previous study also has shown that nurse with higher self-efficacy in managing chronic pain exhibited greater confidence in performing specific pain management tasks, enhancing their overall pain management practices 53 and better adjustment and coping strategies. 54 However, the modest mediating effect of self-efficacy between knowledge, attitudes, and pain management practices suggests the presence of other influential factors not explored in the study such as patientrelated barriers, 29…”
Section: Relationship Between Knowledge Attitude and Pain Management ...mentioning
confidence: 99%